Structural analysis of truck chassis frames under longitudinal loads considering bimoment effects - Al-Hakeem, Ali Hashim (Cranfield University, 1991)
Thin walled beams warp under torsional and longitudinal loads. Warping restraint produces high longitudinal stresses. This is an analysis of the stress distribution in the side members of commercial vehicle chassis frames under the effects of the previously little studied longitudinal loads which may act on a truck chassis through spring hanger brackets. The structure analysed is a model chassis frame consisting of channel section side members and four cross members with different joint connections. The developed theories are incorporated into a special purpose finite element program which may be used in the preliminary stages of chassis frame design. Although the program is only used for the longitudinal load case in this thesis, it is generally applicable for other chassis load cases, including torsion, bending,. .. etc and combination of these. The theoretical results obtained from the program and the finite element analysis on complete chassis frame models are validated against experiments performed on a strain-gauged chassis frame model constructed with the same dimensions and constructional details as the finite element models with the appropriate loading and boundary conditions. Suggestions for the optimum design and attachment positions for components such as spring hanger bracket which may apply longitudinal loads to the side members of the chassis frame are discussed from the point of view of longitudinal loadings.